A practical bio-based reversible permeability control for saturated sands. Issue 6 (15th June 2019) - Hata, Toshiro
Abstract : There is a need for an eco-friendly in situ reversible permeability control that reduces the number of artificial materials used to achieve a saturated sand layer. This study investigates such a control using a method that causes calcite precipitation and decalcification based on the metabolism of carbon sources. This generates carbon dioxide and organic acid and creates and detaches a biofilm using dry yeast and sodium hypochlorite. A pilot test determined the optimal chemical composition for this from a few different concentrations of carbon sources that begin the permeability reduction and recovery process. Following this, the main test (the permeability test) was conducted on a water sample taken from an agricultural area, which was combined with chemicals and dry yeast in a permeameter column. Permeability tests were carried out under three conditions (untreated, treated and treated combined with a biofilm detachment phase). The results suggest that ( a ) calcite precipitation induced by microbes, combined with bioclogging, can control the reduction in soil permeability and ( b ) a biofilm remover (sodium hypochlorite) and decalcification based on the organic acid created from the metabolism of carbon sources effectively recover the soil permeability to its initial state.